INOVASI PENDIDIKAN ISLAM PERSPEKTIF ORANG TUA DALAM PENERAPAN MANAJEMEN MUTU TERPADU DI SDIT CENDIKIA - SUHCROTUL AMIN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
In the era before 2000 the institutionof Islamic education was underestimated. Islamic institutions at that time were only considered alternative schools if they were not accepted into the favorite state education institutions. However, at this time the Islamic education institutions have been able to carry out amazing innovations, not even a few Islamic education institutions have appeared to be superior and quality institutions. One of the factors for the realization of this is due to the implementation of Integrated Quality Management in islamic institutions. Therefore, this research is important to find out the educational innovation Islam perspective of parents in implementing integrated quality management in the Cendikia Integrated Islamic school, Kotawringin Barat Regency, Central Kalimantan. This research is a qualitative research of the field risert type. Data mining using participant observation methods, in-depth interviews and documentation. The source of this research data is the head of Integrated Quality Management. In addition, the author also observed the Terpadi Cendikia Islamic School of Kotawaringin Barat as the place for this study. The findings of this study are that the old man at the Cendikia Kotawaringin Barat Integrated Islamic School thinks that the school managerial has carried out educational innovations, including through the application of Integrated Quality Management, namely management that is oriented towards continuous and continuous improvement by involving all components in the Cendikia Integrated Islamic School , the goal is not only result-oriented but pays more attention to the process to achieve maximum results. The result of the implementation of Integrated Quality Management in the Cendikia Integrated Islamic School is to form, educate, students have character / character karimah, have a trustworthy leader spirit, become a generation ulul a lbab, y that is a generation whose speech is always wet with thought, his heart that always remembers his God, and his intellect that always thinks. ABSTRAKPada era sebelum tahun 2000 lembaga pendidikan Islam dipandang sebelah mata. Lembaga Islam pada masa itu hanya dianggap sebagai sekolah alternatif bila tidak diterima di lembaga pendidikan negeri yang difavoritkan. Namun pada sekarang ini lembaga pendidikan Islam telah mampu melakukan inovasi-inovasi yang mengagumkan, bahkan tidak sedikit lembaga pendidikan Islam yang tampil menjadi lembaga yang unggul dan berkualitas. Salah satu faktor terwujudnya hal tersebut karena penerapan Manajemen Mutu Terpadu di lembaga pendidikan Islam. Karenanya penelitian ini penting untuk mengetahui inovasi pendidikan Islam perspektif orang tua dalam menerapkan manajemen mutu terpadu di sekolah Islam Terpadu Cendikia Kabupaten Kotawringin Barat Kalimantan Tengah. Penelitian ini merupakan penelitian kualitatif jenis field risert. Penggalian data menggunakan metode observasi partisipan, wawancara mendalam dan dokumentasi. Sumber data penelitian ini adalah kepala Manajemen Mutu Terpadu. Selain itu penulis juga mengamati Sekolah Islam Terpadi Cendikia Kotawaringin Barat sebagai sebagai tempat penelitian ini. Temuan penelitian ini bahwa orang tua di Sekolah Islam Terpadu Cendikia Kotawaringin Barat beranggapan bahwa manajerial sekolah sudah melaksanakan inovasi-ivovasi pendidikan di antaranya melalui penerapan Manajemen Mutu Terpadu, yaitu manajemen yang berorientasi pada perbaikan berkesinambungan dan terus menerus dengan melibatkan semua komponen yang ada di Sekolah Islam Terpadu Cendikia, tujuannya tidak hanya berorientasi pada hasil namun lebih memperhatikan proses untuk mencapai hasil maksimal. Hasil dari penerapan Manajemen Mutu Terpadu di Sekolah Islam Terpadu Cendikia adalah membentuk, mendidik, siswa memiliki karakter/ berakhlakul karimah, memiliki jiwa pemimpin yang amanah, menjadi generasi ulul albab, yaitu generasi yang lisannya senantiasa basah dengan zikir, hatinya yang selalu mengingat Tuhannya, serta akalnya yang selalu berfikir.